A Study on Multi-Objective Optimization of Large Deformable Elastic Plates - Kiichiro Sawada; Keigo Kajitani; Tatsuya Uno; Junpei Teramoto; Shingo Komatsu (Buildings, 2022)
Metallic yielding dampers are damaged early before the main frame during earthquakes and take over the damage of the main frame. Under the assumption of the main frame elasticity, both maximum and residual deformation are expected to be reduced. However, the main frame may be damaged, and the assumption of the main frame elasticity may not hold under major earthquakes. However, large deformable elastic plates have larger yielding deformation than standard steel core plates of the damper and can be used as braces to reduce the seismic response of buildings. This study presents a simple definition of design variables for a topology optimization problem involving large deformable elastic plates with rectangular shapes. As bi-objective functions, yielding deformation and yielding force capacity maximization were used. The optimization results were compared with the findings of a previous study. Finally, the efficacy of the braces was verified by experimental tensile tests. The obtained results are as follows. (1) A distinct trade-off relationship was obtained between tensile yielding deformation and tensile yielding load through muti-objective optimizations using the proposed formulation. (2) The Pareto fronts using the proposed formulation were almost identical to the findings of the previous study. (3) While the experimental test results of yielding tensile load are overestimated by the analysis results by the 10 mm rough grid elements, the test results almost correspond to reanalysis results with the 2.5 mm fine grid elements.